Aquilargilla gen. nov., a new genus of Sterrhinae from China with description of two new species (Lepidoptera, Geometridae) - Cui, Le; Jiang, Nan (Zootaxa, 2018)
A new genus Aquilargilla gen. nov., and two new species Aquilargilla ceratophora sp. nov., Aquilargilla basifixa sp. nov. are described from China. Illustrations of adults and genitalia are presented. The new genus is assigned to Scopulini on the basis of the morphological evidence. Comparisons of Aquilargilla with closely related genera are also provided.